Protection Versus Free Trade in the Free State Era: The Finance Attitude. (December 2019) - Devlin, Anna; Barry, Frank
Belief in the benefits of industrial protection had long been a cornerstone of nationalist ideology. Cumann na nGaedheal followed a policy of selective protection while Fianna Fáil was ideologically committed not just to import-substituting industrialisation but to as high a degree of self-sufficiency as possible. The Departments of Finance and Industry and Commerce differed sharply on the costs and benefits of trade restrictions. This article explores the perspective of the Department of Finance and in particular that of J. J. McElligott, Assistant Secretary from 1923 and Secretary of the Department from 1927 to 1953. It demonstrates the strong continuity between his position and that of T. K. Whitaker, who became Secretary in 1956 and whose 1958 report on Economic Development is widely credited with providing the intellectual foundation for the trade liberalisation process of the following decades.